Mediation Without Giving in: Critical Analysis on The UN Convention on Mediation From The Asean Perspective - Herliana, Herliana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
The Mediation Convention is a legal instrument represents final and conclusive dispute resolution outcomes which may be recognized and enforced in accordance with international law. More than 50 countries have ratified the Convention. However, among ASEAN member countries, Indonesia, Thailand, Vietnam, Cambodia and Myanmar have not ratified it.  This paper critically examines what are the legal implications and benefits of the Mediation Convention to ASEAN in the context of an integrated economic community. T his study employs a normative method by doing a library research to obtain secondary data. Data collecting method uses documentary study towards relevant legal materials. The data analysis employs qualitative analysis involving grouping similar kinds of information together in categories. This research concludes that ratification of the Mediation Convention will promote international business and investment in the region. Moreover, to reap benefits of the Convention, ASEAN countries shall meet requirements as follows: supportive external condition, power balance, inclusivity, adaptation to local norm and coherence.